Bridging Humanitarian Responses and Long-Term Development through Transformative Changes—Some Initial Reflections from the World Bank’s Adaptive Social Protection Program in the Sahel - Béné, Christophe; Cornelius, Alex; Howland, Fanny C. (MDPI, 2018)
In the context of increasing climate-related extreme events and other crises, the concept of adaptive social protection (ASP) has been recognized as a potentially effective policy response to reduce the impacts of these shocks and stressors on vulnerable households. The concept is currently being tested at scale by the World Bank in six countries in the Sahel region. Based on conceptual considerations, this paper aims to address three questions: How and to what extent can adaptive social protection be considered transformative? Where does this concept sit along the humanitarian–development continuum? And, how does it relate to resilience? To answer these questions the paper draws on the authors’ exposure to the on-going World Bank ASP program, as well as documents derived from the emerging body of literature on climate- and shock-responsive social protection. Drawing on these different materials the paper first demonstrates that ASP can effectively be considered as a transformative intervention at two different levels: at the system level and at the beneficiaries’ level. The paper also shows how, through its activities designed to strengthen households’ adaptive capacity, an ASP program can contribute to building resilience beyond the short-term coping strategies which humanitarian interventions generally focus on. As such ASP covers a larger spectrum along the humanitarian–development continuum than most other interventions proposed in the context of shock-responsive interventions.